Penguatan Akses Pembiayaan Formal Petani Tembakau melalui Focus Group Discussion antara Petani, Perbankan, Penyuluh, dan OJK di Kabupaten Jember: Strengthening Tobacco Farmers’ Access to Formal Financing through Focus Group Discussions among Farmers, Banks, Agricultural Extension Officers, and the Financial Services Authority (OJK) in Jember. - Anik Suwandari; Mohammad Rondhi; Joni Murti Mulyo Aji; Rokhani Rokhani; julita hasanah; Cindera Rosa Damascena; Rizky Yanuarti (Jurnal Pengabdian Magister Pendidikan IPA, 2026)
Agricultural finance plays a crucial role in supporting productivity and sustainability, particularly in tobacco farming, which is characterized by high capital intensity. Although access to formal financial services has been relatively available, its utilization among farmers remains limited due to various technical, social, and psychological barriers. This community service activity aims to identify key constraints in accessing agricultural finance, explore multi-stakeholder perspectives, and formulate adaptive financing solutions tailored to the characteristics of tobacco farming. A participatory approach was employed through a focus group discussion (FGD) involving tobacco farmers, financial institutions, agricultural extension agents, and the Financial Services Authority (OJK). The activity was conducted in Jember Regency, one of the major tobacco-producing areas in East Java, Indonesia. The results indicate that barriers to accessing finance are not only structural, such as administrative requirements and collateral limitations, but also psychological factors, including fear of loan default and social stigma associated with formal borrowing. Additionally, financing is often used for household consumption rather than productive activities, reducing its effectiveness in supporting farm performance. From the supply side, financial institutions face high risks due to production uncertainty and price volatility, while regulators emphasize the importance of improving financial literacy among farmers. The FGD facilitated the integration of perspectives among stakeholders, leading to shared understanding and context-specific solutions. This study highlights that enhancing financial inclusion in the agricultural sector requires a collaborative approach, strengthening financial literacy, and developing flexible financing schemes aligned with seasonal farming patterns.